Qualitative Findings on the Impact of Debate Techniques on English Language Speaking Competence - Ronaldo Masti Tarigan; Yani Lubis (Universitas Negeri Semarang, 2024)
Debate techniques are widely recognized for their potential to enhance students' speaking skills and critical thinking abilities. This study aims to investigate the impact of debate techniques on English language speaking competence among students. Conducted at an English language learning center in Medan, this qualitative research employs classroom action research methods over a one-month period. Data were collected through observations, interviews, and document analysis. The findings indicate significant improvements in students' speaking skills, including increased confidence, fluency, and ability to construct and defend arguments. The debate techniques fostered an engaging learning environment, promoting active student participation and critical thinking. The results show that, across three cycles of debate-based instruction, students' average speaking scores increased notably, and all participants achieved the required competency levels by the final cycle. This study concludes that incorporating debate into language learning curricula can significantly enhance speaking competence. The research contributes to educational science by providing evidence that debate techniques are an effective pedagogical tool for improving oral communication skills in English, thereby supporting their integration into language education programs.